2002
DOI: 10.1007/s00418-002-0470-7
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal, enteric neurons, and smooth muscle and myoid cells of the murine gastrointestinal tract express full-length dystrophin

Abstract: A gene located on the X chromosome is responsible for the transcription of several mRNA and related dystrophin isoforms. Lack or truncated expression of the 427-kDa, full-length isoform in skeletal muscle results in Duchenne muscular dystrophy (DMD). Patients with DMD, as well as mdx mice, a mutant strain also lacking this isoform, show gastrointestinal dismotilities. The present aim was to identify the cell types that express full-length dystrophin in the gastrointestinal tract. An immunohistochemical study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…It was recently demonstrated that the gastric ICC of the mouse express dystrophin, in particular the full‐length isoform of dystrophin (Vannucchi et al, 2002). We presently found that gastric ICC in mdx mice were missing this isoform and showed ultrastructural changes consisting in: the presence of a very large Golgi apparatus, significantly more numerous coated vesicles and pits either at the cell surface or at the budding face of the Golgi apparatus, mithocondria larger than in controls, and dilated RER cisternae, together with a significantly lower number of caveolae and a reduction in the SER extension and intermediate filaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that the gastric ICC of the mouse express dystrophin, in particular the full‐length isoform of dystrophin (Vannucchi et al, 2002). We presently found that gastric ICC in mdx mice were missing this isoform and showed ultrastructural changes consisting in: the presence of a very large Golgi apparatus, significantly more numerous coated vesicles and pits either at the cell surface or at the budding face of the Golgi apparatus, mithocondria larger than in controls, and dilated RER cisternae, together with a significantly lower number of caveolae and a reduction in the SER extension and intermediate filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the full‐length isoform of dystrophin has been reported to be expressed in all gastrointestinal ICC in the mouse (Vannucchi et al, 2002) and, therefore, the possibility that these cells might be involved in gastric motility disorders of mdx mice has to be taken into account. The present study was undertaken to verify, at first, whether the gastric ICC undergo morphological changes in mice lacking dystrophin.…”
mentioning
confidence: 99%
“…It is known that dystrophin is present in several cell types in the gastrointestinal wall, in smooth muscle cells (SMCs) of the muscularis externa and muscularis mucosae, in the myoid cells located in the mucosa, in the perivascular SMCs, and all the submucous and myenteric neurons [52]. On the contrary, full-length dystrophin is lacking in the gastrointestinal tract of DMD patients and mdx mice, which show several alterations in gastrointestinal motility.…”
Section: Discussionmentioning
confidence: 99%
“…36 Both smooth muscle and enteric neurons express the dystrophin gene, and slow intestinal transit has been documented in the dystrophic (mdx) mouse model. 37,38 Associated strongly with a history of constipation, chronic intestinal pseudo-obstruction (CIPO) is a problem that can severely affect quality of life in DMD. CIPO is characterized by abdominal pain and distension associated with the inability to defecate.…”
Section: Constipationmentioning
confidence: 99%